SrSnO3 Perovskite post-deposition on Ag-doped TiO2 rutile nanoflower for optoelectronic application - Ishak, Nurul Najihah; Nayan, Nafarizal; Megat Hasnan, Megat Muhammad Ikhsan; Abd Hamed, Noor Kamalia; Md Yunos, Yusri; Mohamed Ali, Mohamed Sultan (Elsevier, 2023)
Optoelectronic nanomaterials could be improved through bandgap engineering and surface area enhancement, which involves depositing nanoparticles on their photoactive layer surfaces. The present study investigated silver-doped rutile nanoflower TiO2 with an additional surface layer of perovskite SrSnO3 nanoparticles (rT-NF) using a combination of hydrothermal pre-processing followed by radio frequency (RF) magnetron sputtering. The new structure exhibited expanded visible spectrum light absorption. Increasing SrSnO3 deposition time lowered the energy bandgap from 3.0 eV to 2.89 eV. Furthermore, the electrical impedance approach and current-voltage measurement revealed the material’s electrical properties, subsequently supported by structural and surface characterization via XRD, FESEM, AFM, and Raman Spectroscopy. The post-deposition of SrSnO3 perovskite on Ag-doped rT-NF raised rutile crystallinity, enhanced its photo response, and lowered its bandgap and bulk resistivity. The outcomes of this work provided a new route to enhancing standard TiO2 nanoflower photoelectric response via perovskite post-deposition on nanoflower surfaces